“A republican independence? Towars a republican history of the independence” - Mourão, Gonçalo de Barros Carvalho e Mello (Revista do Instituto Histórico e Geográfico Brasileiro, 2023)
Federalist constitutional republicanism was the primary driving force behind Brazil's independence. It brought about the political and social inevitability of separation from Portugal, and constrained absolutist monarchism to adopt the path of monarchical independence by enthroning the Braganza dynasty, abandoning, thus, the options to maintain a union with Portugal. Testimonies from the time demonstrate how fear and even terror of republican, constitutionalist liberal and federalist ideas and movements, initiated in Brazil by the Revolution of 1817, led to the adoption of the monarchical solution, wherein absolutism was veiled by the moderating power